Background similarities and differences in business performance among family and non-family franchisees in Malaysia - Mohd Hizam, Hanafiah; Nurul Ashykin, Abd Aziz (Penerbit Universiti Sains Malaysia, 2023)
Franchising business has been growing rapidly in Malaysia after the government launched the Franchise Development Programme in 1992, establishing the Franchise Division in 1995 and introducing the Franchise Act 1998. Nowadays, Malaysia has 870 registered franchising systems with 60 home-grown franchise systems successful in penetrating 55 countries. Besides the fascinating development of this industry, the main gap in academic research is that very rare research has been conducted to study franchising business owned by family businesses. Therefore, the objectives of this study are to investigate the similarity in personal background and differences in business performance, between family business franchisee and non-family business franchisee. Hence, a survey among 204 franchisee entrepreneurs in Malaysia has been conducted through a self-administered questionnaire with 90 of them being considered as family business franchisees and 114 as non-family business franchisees. Based on statistical analysis, this study found that personal background such as educational level, working experience, total investment and dependency on franchising business are not significant in comparing family business franchisees and non-family business franchisees. Further, perception of success and intention to remain in the franchising business is also not significant in assessing family business franchisees and non-family business franchisees. However, this study found that non-family business franchisees have better business performance, in terms of sales performance and number of employees, compared to family business franchisees.